The properties of mid infrared surface modes at the interface of air and one dimensional ternary photonic crystal. (December 2021) - Kumar, Mahendra; Prasad, Surendra
Abstract: In the present manuscript, theoretical design of truncated one dimensional ternary photonic crystal is proposed for analyzing the properties of transverse electric (TE) surface modes viz. band structures, its localization in photonic band gaps (PBGs), field profiles and energy carried by these modes. The periodicity of the structure (comparable to the wavelength of incident electromagnetic waves) is chosen as such the modes are localized in mid-infrared frequency domain ( 600 cm − 1 to 1800 cm − 1 or 5 μ m to 16 μ m ). The dispersion relation of surface modes is derived by using continuity condition of tangential components of electric and magnetic fields and transfer matrix method. It is found that by varying the cap layer thickness d c and thickness of first layer d t of each unit cell, surface modes are either strongly (near center of PBG with decay length 8.8 μ m ) or weakly (near edge of PBG with decay length 42.5 μ m ) bounded to the interface. The energy carried by the surface modes along the interface plane is around 3 . 3 m J while across the interface plane it is of the order of 10 − 14 . It has been proved that the material rich modes ( 2 V / m ) have high field enhancement compared to material deficient modes ( 1 V / m ). The study stresses on different aspects of the proposed model that can be sought for suitable practicable applications in mid-infrared photonics, especially in design of mid-infrared bio-chemical sensors, mid-infrared temperature sensors, waveguides, omnidirectional reflectors, optical filters, band edge lasers, multiplexers, mitigators, compensators, etc. Highlights: The properties of mid infrared surface modes are investigated. The modes present at or near the edges in a particular PBG are loosely bound. The modes localized at the center have higher electric field at the interface. Material rich modes decay comparatively faster than material deficient modes.